Historiografi Novel Sejarah - Gunawan, Rudy; Rachmah, Huriah (Jurnal Sejarah Indonesia, 2025)
History is a science that has many meanings for everyone. In learning history aims to foster a sense of nationalism and pride in one's homeland. The purpose of the study is to explain the narrative of Indonesian-centric historiography in historical novels in Indonesia. This study follows the historical research procedure with the stages of heuristics, criticism, interpretation, and historiography. This study shows that history has a method, namely systematic principles and rules designed to help collect historical source materials efficiently, disseminate or critically examine these sources, and present conclusions in written form to increase historical awareness. Historical awareness can emerge in various ways, for example by getting to know local history, joining a history community to find historical sources, or reading historical novels. Historical novels can broaden readers' horizons about history because they also include stories, interpretations, and experiences of the author. As a result, reading history is more enjoyable for readers.